Interferensi Bahasa Dalam Muhadatsah Yaumiyah Santri Putri Tingkat SMA Pondok Pesantren Darurrahmah Gunung Putri Bogor - Siti Muslikah; latifah - khoiriah (Bahasa dan Sastra Arab, Fakultas Adab dan Humaniora, UIN Sunan Gunung Djati, 2024)
Arabic language in modern Islamic boarding schools has become a separate existence to be learned. The students at the darurrahmah Islamic boarding school are required to master Arabic as a second language and used as a means of daily communication for students. This study seeks to find out the types of interference and the factors behind the occurrence of interference in the muhadatsah yaumiyah of female students at the high school level of the Darurrahmah Islamic boarding school. This research method is descriptive with field research. Data collection techniques are carried out by observation, documentation and interviews. The results obtained in this study showed that female students at the high school level of the Darurrahmah Islamic Boarding School experienced 4 types of interference, namely phonological interference in the pronunciation of letter sounds, syntactic and morphological interference in the appropriateness of the use of sentences and their positions and semantic interference in the selection of vocabulary that was absorbed by the meaning Keywords: Arabic language, Interference, Islamic boarding school.